Evaluation of injectable metamizole utilization in children and adults in primary care - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 2020)
Objective: Use of injectable metamizole in the outpatient setting is controversial due to safety concerns. We aimed to compare injectable metamizole prescribing patterns for children and adults with further evaluation of nationwide metamizole consumption trend. Materials and methods: In this retrospective cross-sectional study, 100 injectable drug-containing prescriptions written in each month of 2010 in 32 provinces of Turkey were selected. Drug utilization patterns on injectable metamizole-containing prescriptions (n = 1,270) were analyzed and compared by pediatric and adult groups. Additionally, nationwide outpatient consumption data from 2010 to 2018 were obtained. and the utilization trend was examined. Results: Children received 12.4% of injectable metamizole-containing prescriptions. Male predominance was observed in children (62.7%), as opposed to female predominance in adults (55.2%, p < 0.05). The most frequent diagnoses were acute tonsillopharyngitis and acute bronchitis in both groups. Single-diagnosis prescriptions constituted 79.1% of the pediatric group and 53.1% of the adult group (p < 0.05). Diagnoses, drugs, and injectable analgesics per prescription were significantly higher in adults (1.68 +/- 0.86, 3.45 +/- 0.90, and 1.06 +/- 0.23, respectively) than in children (1.22 +/- 0.43, 3.25 +/- 0.88, and 1.00, respectively) (p < 0.05). The percentage of prescriptions containing injectable antibiotics was higher in children (83.6%) than in adults (64.9%). Outpatient injectable metamizole consumption showed a decreasing trend in 2010 - 2018. Conclusion: Despite recent downward trend, prescribing of injectable metamizole in primary care was considerably prevalent. This study, which highlights fundamental differences among metamizole utilization patterns in children and adults, addresses the inadequacy of rational use of the drug in terms of preferred indications and accompanying drugs.
Keywords: injectable analgesics; dipyrone; pediatrics; primary health care; drug utilization; DIPYRONE; PARACETAMOL; PATIENT; GENDER; SEX